Measuring Uncertainty and its Strategic Implications - Kundu, Amit; Bhattacharya, Arabinda (Prabandhan: Indian Journal of Management, 2017)
The study explored the measure of uncertainty of the market and also the linkage between the uncertainties of the business environment and the performance of the organizations in the specified sector that includes chemical ; petro - chemical process industry; agriculture related industry; processed food industry; bio - chemical related industry in the context of liberalized Indian economy. In this paper, the measure of uncertainty on the basis of subjective understanding of managers was validated by the objective measure of market uncertainty. The strong relationship between two measures of uncertainty was established and the subjective measure of uncertainty had a strong impact on the performance of the organization. The subjective measure has been classified into two dimensions, namely, internal uncertainty and external uncertainty. The paper also ascertained the relative influence of internal uncertainty (IU) and external uncertainty (EU) on the performance of the organization. The study also established that internal uncertainty has a greater impact than external uncertainty on the performance of the organization. Through this analysis, it is possible to ascertain how the organizations are able to combat the uncertain situation in the market for better performance.